Understanding the selectivity in silico of colistin and daptomycin toward gram-negative and gram-positive bacteria, respectively, from the interaction with membrane phospholipids - Aristizabal, Yesid; Liscano, Yamil; Oñate-Garzón, José (Frontiers in Bioinformatics, 2025)
Antimicrobial resistance is a significant public health concern worldwide. Currently, infections by antibiotic-resistant Gram-negative and Gram-positive bacteria are managed using the lipopeptide antibiotics colistin and daptomycin, which target the microbial membrane. Despite the fact that both are short, cyclic, and have a common acylated group, they display remarkable antimicrobial selectivity. Colistin exhibits activity only against gram-negative bacteria, while daptomycin only against gram-positive bacteria. However, the mechanism behind this selectivity is unclear. Here, we performed molecular dynamics simulations to study the interactions between Escherichia coli membrane models composed of 1-Palmitoyl-2-Oleoyl-sn-Glycero-3-Phosphoethanolamine (POPE)/1-Palmitoyl-2-Oleoyl-sn-Glycero-3-Phosphoglycerol (POPG) with daptomycin and colistin, independently. Similarly, we simulated the interaction between the Staphyloccocus aureus model membrane composed of POPG and cardiolipin (PMCL1) with both antibiotics. We observed that colistin interacted via hydrogen bonds and electrostatic interactions with the polar head of POPE in E. coli membrane models, mediated by 2,4-diaminobutyric acid (DAB) residues, which facilitated the insertion of its acyl tail into the hydrophobic core of the bilayer. In S. aureus membrane models, weaker interactions were observed with the polar head, particularly POPG, which was insufficient for the insertion of the lipid tail into the membrane. However, daptomycin displayed strong interactions with several POPG functional groups of the S. aureus membrane model, which favored the insertion of the fatty acid tail into the bilayer. Contrastingly, daptomycin showed negligible interactions with the E. coli membrane, except for the amino group of the POPE polar head, which might repel the calcium ions conjugated with the lipopeptide. Based on these results, we identified key amino acid-phospholipid interactions that likely contribute to this antibacterial selectivity, which might contribute to designing and developing future antimicrobial peptides.